2011
DOI: 10.1542/peds.2010-3343
|View full text |Cite
|
Sign up to set email alerts
|

Children With Asthma Hospitalized With Seasonal or Pandemic Influenza, 2003–2009

Abstract: The majority of asthmatic children hospitalized with influenza have no additional medical conditions. Complications such as pneumonia and need for intensive care occur in a substantial proportion, highlighting the importance of influenza prevention through vaccination among asthmatic children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
64
3
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 10 publications
3
64
3
2
Order By: Relevance
“…Novel functions for eosinophils in cancer (32), cardiac disease (33), and diabetes (34), among others, indicate that eosinophils and their role in immunity are complex and extend beyond that of allergic diseases. Recent reports surrounding the 2009 influenza pandemic provide evidence that asthmatics were less likely to suffer severe morbidity compared with non-asthmatics (4,5,7,35). Mice sensitized and challenged with A. fumigatus and infected during peak airway inflammation were protected from influenza, marked by the absence of weight loss, enhanced viral clearance, and increased infiltration of virus-specific CD8 + T cells into the airways (13).…”
Section: Discussionmentioning
confidence: 99%
“…Novel functions for eosinophils in cancer (32), cardiac disease (33), and diabetes (34), among others, indicate that eosinophils and their role in immunity are complex and extend beyond that of allergic diseases. Recent reports surrounding the 2009 influenza pandemic provide evidence that asthmatics were less likely to suffer severe morbidity compared with non-asthmatics (4,5,7,35). Mice sensitized and challenged with A. fumigatus and infected during peak airway inflammation were protected from influenza, marked by the absence of weight loss, enhanced viral clearance, and increased infiltration of virus-specific CD8 + T cells into the airways (13).…”
Section: Discussionmentioning
confidence: 99%
“…[234] Underlying conditions also put children at risk for longer hospitalization stays, compared to children without underlying conditions, [235] and are frequently present among fatal cases of influenza virus infection among children. [236] Among adults with acute exacerbations of chronic obstructive pulmonary disease (COPD), a systematic review found that RT-PCR-confirmed influenza was associated with 7% of cases, and with highest number of respiratory viruses detected in Europe, but a highest proportion of influenza relative to other viruses in Asia.…”
Section: Disease Burdenmentioning
confidence: 99%
“…2 In high-income countries, 3% to 18% of pediatric admissions to the hospital are due to LRTI, 3,4 and among pediatric LRTI hospitalizations, 3% to 14% have been reported to require admission to an ICU. [5][6][7][8][9] Data on rates of pediatric hospitalizations for severe LRTI, including those requiring specialized care, such as ICU or mechanical ventilation, are limited. Such information might be useful for public health emergency planning for pandemics and other emerging respiratory infections, such as Middle East respiratory syndrome coronavirus.…”
mentioning
confidence: 99%